Imaging of pediatric stroke - Sivaswamy, Lalitha; Altinok, Deniz; Juhász, Csaba (Journal of Pediatric Neurology, 2010)
Multiple modalities for imaging of pediatric stroke are available, though not all have clinical application in acute stage. In this article, we review the relative advantages and disadvantages of imaging methods designed to visualize the brain parenchyma, arteries, veins as well as the penumbra in arterial and venous ischemic events of childhood and perinatal strokes. The applications of diffusion-weighted magnetic resonance imaging (MRI) in the setting of neonatal stroke have led to a better understanding of the extent of damage in a relatively early stage, which helped to overcome certain limitations of cranial ultrasound. Comparative analysis between MRI including T2* gradient echo images, and computed tomography in hemorrhagic stroke has changed the commonly held belief that cranial computed tomography is superior to MRI in this clinical scenario. Susceptibility perfusion MRI and arterial spin labeling methods have been applied successfully in adult strokes; however, their introduction into the pediatric realm has been limited. Finally, the employment of diffusion tensor imaging,
Keywords: Pediatric stroke; computed tomography; magnetic resonance imaging; diffusion weighted imaging; positron emission tomography